Reviving Economic Recession and The Role of Insurance Companies in Nigeria - Akeem Oladeinde Raji; Ayodeji Najeem Isiaka; Olufawo Henry Siji (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2023)
The persistent reoccurring of poor economic conditions during the economic recession has put the policymaker on the appropriate approach to tackle the economic problem. Despite the efforts to curb the menace, the economy is still vulnerable to shocks; therefore, this study investigated the role of insurance companies in reviving the economic recession in Nigeria. The study covers the period of 25 years from 1996 to 2020. Data on economic recession was proxied with dummy when 0 represents the period of positive economic growth rate while 1 represent the period of negative growth rate. Data on insurance investment, insurance asset, number of insurance companies and insurance contribution to GDP that measured with insurance performance were considered as independent variables. Ordinary Least Square method was employed and the result revealed that insurance asset does not capable of reducing economic recession while insurance investment, insurance performance and number of insurance companies proven to be sufficient to reduce economic recession. Based on the findings, the study concluded that insurance companies played a significant role in reviving economy from recessionary issues. The study recommended that adequate attention should be given to insurance companies in to fulfill their full potential